Miss representation - Siebel Newsom, Jennifer; Dietrich, Claire; Costanzo, Julie; Congdon, Jessica; Roco Films Educational (Firme); Girls Club Entertainment (Girls Club Entertainment, 2011)
Like drawing back a curtain to let bright light stream in, MISS REPRESENTATION uncovers a glaring reality we live with every day but fail to see. Written and directed by Jennifer Siebel Newsom, the film exposes how mainstream media contributes to the under-representation of women in positions of power and influence in America. The film challenges the media’s limited and often disparaging portrayals of women and girls, which make it difficult for women to achieve leadership positions and for the average woman to feel powerful herself. In a society where media is the most persuasive force shaping cultural norms, the collective message that our young women and men overwhelmingly receive is that a woman’s value and power lie in her youth, beauty, and sexuality, and not in her capacity as a leader. While women have made great strides in leadership over the past few decades, the United States is still 90th in the world for women in national legislatures, women hold only 3% of clout positions in mainstream media, and 65% of women and girls have disordered eating behaviors.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; cinéma; communication; corps; cours; discipline; documentaire; féminisme pop; premier cycle; périodes historiques; représentation des femme*; régions géographiques; santé; sex2283; sexualité; thématiques; travail; états-unis

La chirurgie mammaire et l'esthétiquement correct : le sein et les médias - Le Louarn, S.; Le Louarn, C. (Annales de Chirurgie Plastique Esthétique, 2005)
Résumé Cet article discute en quoi les normes du sein esthétiquement correct, les caractéristiques physiologiques du sein, l'allongement de la durée de vie et les possibilités de la chirurgie esthétique influencent la demande de modification mammaire. Puis il examine comment le sujet des modifications mammaires est traité dans différents médias : presse écrite (notamment féminine), documentaires et spectacles de téléréalité. Il constate un paradoxe entre d'une part, un contexte social qui durcit des normes, encourage la quête du bien-être et la réalisation de soi et prône la tolérance et, d'autre part, la réalité d'un certain déni du droit des femmes à choisir leur apparence mammaire. L'article tente de décrypter les obstacles historiques, philosophiques, sociaux, religieux et idéologiques impliqués. Enfin, il propose une nouvelle grille de lecture du positionnement d'un individu par rapport à la chirurgie esthétique selon deux axes : le « Faire » et le « Dire ». Cette grille pourra aider le chirurgien plasticien à mieux décoder la demande de chaque patiente, pour mieux la satisfaire.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; corps féminin; cours; discipline; discours médiatique; esthétique; europe; france; féminisme pop; hétérosexisme; occident; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques